EFEK PLATFORM PEMBELAJARAN VIRTUAL TERHADAP PENINGKATAN KETERAMPILAN MAHASISWA DALAM MERANCANG DAN MEMPRODUKSI APLIKASI ONLINE VIRTUAL LABORATORY - Nofri Hendri; Septriyan Anugrah (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
The increasingly widespread use of virtual learning applications in educational institutions requires educators to improve their skills in designing and producing these applications. A new VLP is proposed in this study to cultivate students' skills in designing and producing an online virtual laboratory (OVL). To test the effect of VLP, 30 students of the Educational Technology Study Program FIP UNP who took the Computer Fundamentals course for the July-December 2020 Semester participated in this study using a pre-test and post-test. Data were collected using online instruments; achievement tests, performance observation cards, product evaluation cards, and usability questionnaires. The results showed that the proposed VLP was effective in increasing students' knowledge and practical skills needed to design and produce OVL. Students find VLP a convenient way to learn relevant knowledge and skills. Keywords: Virtual Learning Platform; Online Virtual Laboratory; Education technology; Design Skills